2011
DOI: 10.4136/ambi-agua.696
|View full text |Cite
|
Sign up to set email alerts
|

Application of multivariate statistical techniques to evaluate organic pollution on a river in Argentina

Abstract: The aim of this paper was the application of multivariate statistical techniques to evaluate spatial and temporal variations in the water quality of Potrero de los Funes River using physical, chemical and bacteriological parameters and select the most significant parameters of organic pollution in the river in order to implement in the future water quality monitoring. The river was monitored regularly at three sites: RP1, RP2 and RP3, over the period 2008–2009, for 16 parameters. The complex data matrix was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
8
0
4
Order By: Relevance
“…The contribution of variations in dissolved oxygen and temperature was minor but significant. Previous studies have shown a deterioration of surface waters downstream from PR2, coincides spatially with the most urbanized part of the town and temporally with the increase of tourist activities during the summer season (Oliva González et al, ). Almeida et al () applied a General Quality Index calculated from 11 parameters, including bacteriological measurements and likewise reported a decline of water quality in zones of the river located in the urbanized area of Potrero de los Funes town.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The contribution of variations in dissolved oxygen and temperature was minor but significant. Previous studies have shown a deterioration of surface waters downstream from PR2, coincides spatially with the most urbanized part of the town and temporally with the increase of tourist activities during the summer season (Oliva González et al, ). Almeida et al () applied a General Quality Index calculated from 11 parameters, including bacteriological measurements and likewise reported a decline of water quality in zones of the river located in the urbanized area of Potrero de los Funes town.…”
Section: Discussionmentioning
confidence: 91%
“…Site PR1 was considered as the reference site. Previous studies assessed PR1 as the area of environmental base line of water quality on the basis of physical–chemical and bacteriological analysis (Oliva González et al, ). PR1 also represents the initial stretch of PR, where its two tributaries streams converge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…La literatura muestra que a la hora de generar un programa para el análisis de la calidad del agua en un reservorio acuático, los parámetros bio-físicos comúnmente seleccionados son la concentración de clorofila-a, los sedimentos en suspensión y la transparencia del agua (Zhu et al, 2005;Gonzalez et al, 2011). La transparencia del agua, es expresada como el límite de la zona fótica (z-fot).…”
unclassified